Case Report: Bilateral Choroidal Neovascular Membranes in a Patient With a Delayed Diagnosis of Acute Syphilitic Posterior Placoid Chorioretinopathy - Schimansky, Sarah; Burke, Tomás (Frontiers in Ophthalmology, 2022)
We report the case of a 78-year old man with a delayed diagnosis of syphilis and an advanced phenotype of acute syphilitic posterior placoid chorioretinopathy after receiving 5 months of high dose steroids prior to anti-treponemal treatment. Bilateral choroidal neovascular membranes were present at the time of diagnosis and were successfully treated with intravitreal aflibercept, following completion of anti-treponemal therapy.